2021
DOI: 10.3390/microorganisms9030574
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of ToRCH Pathogens in Southeast Asia

Abstract: ToRCH is the acronym for several pathogens associated with pregnancy complications and sequelae in the unborn or newborn child. Particularly primary infections during pregnancy are associated with increased risk. Seroprevalence data of ToRCH infections are important, especially in countries with weak disease surveillance systems, to estimate immunity and vaccination levels, as well as exposure rates and thus the risk of infection during pregnancy. A systematic literature search spanning a 30-year time period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
0
2
1
Order By: Relevance
“…On the other hand, the final report of this study is lower than previously reported in the Lao People's Democratic Republic (79.7%) ( 31 ) and in Nigeria (81.1%) ( 32 ). The variation in TT vaccine coverage rates could be attributed to cultural differences, health-seeking behavior, healthcare coverage, economic and infrastructural access, and the impact of war.…”
Section: Discussioncontrasting
confidence: 92%
“…On the other hand, the final report of this study is lower than previously reported in the Lao People's Democratic Republic (79.7%) ( 31 ) and in Nigeria (81.1%) ( 32 ). The variation in TT vaccine coverage rates could be attributed to cultural differences, health-seeking behavior, healthcare coverage, economic and infrastructural access, and the impact of war.…”
Section: Discussioncontrasting
confidence: 92%
“…While Toxoplasma gondii (T. gondii), rubella virus and cytomegalavirus (CMV) cause mostly asymptomatic or mild symptoms in pregnant women, they can cause serious clinical pictures by passing to the fetus. In order to prevent serious consequences such as fetal anomalies, premature birth, stillbirth and postnatal chronic infections, it is important to diagnose the disease quickly and accurately and to monitor the fetus (1). In addition, awareness of these diseases will enable clinicians to counsel the mother to protect her from these factors, and it will be useful to tell the family about negative fetal outcomes when infection occurs (2).…”
Section: Introductionmentioning
confidence: 99%
“…The TORCH test, also known as the TORCH panel, is an acronym for toxoplasmosis, rubella, and cytomegalovirus and includes other infections like herpes simplex varicellazoster and syphilis. This test screens for the presence of IgM and IgG antibodies during pregnancy to determine the immune status of the mother where if IgG antibodies are present at a specific concentration, then it indicates immunity against Toxoplasma gondii, rubella, cytomegalovirus, and herpes simplex virus, ruling out infection transmission to the fetus (19).…”
Section: Investigationsmentioning
confidence: 99%